PENGGUNAAN MEDIA PEMBELAJARAN DALAM PROSES PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) di MADRASAH IBTIDAIYAH (MI) - Syifa Sa'adiah; Oman Farhurohman (Ibtida’i, 2020)
Islamic cultural history lessons (SKI) are lessons related to past events. From the SKI material, students are expected to be able to recognize, understand, live the history of Islamic culture, which contains the values ​​of wisdom to be used to train intelligence, shape the attitudes, character and personality of students. In fact SKI is often considered a boring subject, it is due to various reasons one of which is in the SKI learning process the lack of use of learning media. Therefore, a teacher is required to be more creative and innovative in providing lessons to students so as to create an effective and enjoyable learning process. The application of innovative learning designs accompanied by the use of supportive learning media can help a teacher deliver material so that it is easier to understand and certainly appeals to students who receive it. The types of instructional media that can be used in SKI learning in MI consist of 3 kinds, namely visual media which can be in the form of images, audio media that can be in the form of recordings and audio visual media which can be in the form of historical films or documentaries about the history of Islamic culture. Islamic cultural history lessons (SKI) are lessons related to past events. From the SKI material, students are expected to be able to recognize, understand, live the history of Islamic culture, which contains the values ​​of wisdom to be used to train intelligence, shape the attitudes, character and personality of students. In fact SKI is often considered a boring subject, it is due to various reasons one of which is in the SKI learning process the lack of use of learning media. Therefore, a teacher is required to be more creative and innovative in providing lessons to students so as to create an effective and enjoyable learning process. The application of innovative learning designs accompanied by the use of supportive learning media can help a teacher deliver material so that it is easier to understand and certainly appeals to students who receive it. The types of instructional media that can be used in SKI learning in MI consist of 3 kinds, namely visual media which can be in the form of images, audio media that can be in the form of recordings and audio visual media which can be in the form of historical films or documentaries about the history of Islamic culture.